Predisposing factors to the appearance of complications in patients with traumatic brain injury - Barrios, Leonardo; Cortes-Valenzuela, Daniela; Palma-García, Francisco; Vega Medina, Pablo Andres; Vincensini, Juan David; Restrepo Govea, Jezreel (Revista Argentina de Neurocirugía, 2024)
Background: Traumatic brain injury is one of the main causes of disability and death. Objectives: to identify predisposing factors for the occurrence of complications in patients with traumatic brain. Methods: an observational, analytical, retrospective case-control study was conducted on patients diagnosed with traumatic brain injury classified by severity according to the Glasgow Coma Scale between 2018 and 2022. Clinical and demographic variables were analyzed using the statistical software Epi Info version 7.2, and Fisher’s Exact Test was applied to determine significant associations. Results: a total of 118 patients were included, with 38.13% developing complications. Factors associated with a higher risk of complications were the neurological impairment measured by the Glasgow Coma Scale during hospitalization (OR = 63.88, 95% CI: 8.15-500.39, p <0.0001) and the initial severity of the traumatic brain injury (OR = 76.32, 95% CI: 9.75-597.67, p <0.0001). No significant associations were observed for other variables, such as sex, time of arrival, or the presence of intracranial hematomas. Conclusion: the results indicate that neurological impairment and the initial severity of the traumatic brain injury are keys factors in the occurrence of complications in patients with traumatic brain injury.